2009
DOI: 10.1071/nb08014
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of prophylaxis for measles contacts in NSW

Abstract: Post-exposure immunisation remains an effective tool for preventing secondary cases of measles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 6 publications
0
16
0
5
Order By: Relevance
“…At the individual level, administration of measles vaccine within 72 hours of initial exposure may avert or modify the clinical course of the illness, and is generally recommended as a preventive tool in elimination settings (Table 1). 1-4 Recent studies have confirmed a benefit from this intervention, with effectiveness of post-exposure immunization ranging between 91%–100%, 54 , 55 corroborating observations made in the pre-elimination era. 56-59 Two studies showing no protection from vaccine prophylaxis were limited by a small sample size 60 or by delayed vaccine administration in relation to measles exposure.…”
Section: Containment Strategies — Guidance Evidence Challenges and mentioning
confidence: 67%
See 1 more Smart Citation
“…At the individual level, administration of measles vaccine within 72 hours of initial exposure may avert or modify the clinical course of the illness, and is generally recommended as a preventive tool in elimination settings (Table 1). 1-4 Recent studies have confirmed a benefit from this intervention, with effectiveness of post-exposure immunization ranging between 91%–100%, 54 , 55 corroborating observations made in the pre-elimination era. 56-59 Two studies showing no protection from vaccine prophylaxis were limited by a small sample size 60 or by delayed vaccine administration in relation to measles exposure.…”
Section: Containment Strategies — Guidance Evidence Challenges and mentioning
confidence: 67%
“…54 Thus, successful implementation of this strategy requires a close working relationship between healthcare providers and public health specialists and the rapid identification and reporting of cases through active surveillance. 54 , 55 …”
Section: Containment Strategies — Guidance Evidence Challenges and mentioning
confidence: 99%
“…Considering the time until immunity in vaccinated individuals develops, two recent studies have shown an effective measles post-exposure prophylaxis (PEP) of 90 . 5% and 100 %, respectively, if conducted within 72 h [18,19]. In individuals who developed measles despite PEP, two other studies observed a maximum time-interval from receiving PEP to the development of measles of y10 days [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…En effet, plusieurs études ont montré l'efficacité des immunoglobulines chez les sujets à risque dans les six jours suivant l'exposition à un cas confirmé de rougeole [44,[63][64][65] [65].…”
Section: Conduite à Tenir Chez La Femme Enceinteunclassified